How to conduct qualitative research in social science - Liamputtong, Pranee (How to research guides, 2023)
"This book offers insights into key research-based strategies that can help to alleviate global challenges faced by both individuals and groups in society. Focusing on conducting qualitative research, the chapters highlight an approach for understanding human thoughts and actions, and examining how things actually function in society. Explaining both the theoretical and practical aspects of doing qualitative research, the book uses examples from real-world research projects to emphasise how to conduct qualitative research in the social sciences. Pranee Liamputtong draws together contributions covering qualitative research in cultural and medical anthropology, sociology, gender studies, political science, criminology, demography, economic sciences, social work, and education. Each chapter discusses the essence of a discipline before examining the contribution of qualitative enquiry and then interrogating traditional qualitative research methods as well as emerging or innovative methods. This will be an invigorating read for students and scholars of the social sciences. Its combination of theoretical and practical insights will also be essential for qualitative researchers"--